1980
DOI: 10.1007/bf00292422
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the DNA content in translocated regions of Drosophila polytene chromosomes

Abstract: The DNA content of translocated polytene chromosome regions in Drosophila melanogaster is affected by heterochromatic position effect. Microdensitometric studies on wm258-21 translocation heterozygotes showd (Hartmann-Goldstein and Cowell, 1976; Cowell and Hartmann-Goldstein, 1980) that band region 3D1-E2, adjacent to the breakpoint, contained less DNA than the homologous non-translocated region whereas the neighbouring 3C1-10 region contained more DNA than its non-translocated counterpart. In the nuclei selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Although small reductions in DNA content were reported previously in some cases (Schultz, 1941;Ananiev and Gvozdev, 1974;Cowell and Hartmann-Goldstein, 1980;Kornher and Kaufman, 1986) other workers detected no evidence for changes in copy number (Cole and Sutton, 1941;Henikoff, 1961;Rushlow et al, 1984). Most measurements were made at an unknown distance from the inducing breakpoint.…”
Section: A Variegated Position Effect Reduces the Copy Number Of Somementioning
confidence: 84%
See 1 more Smart Citation
“…Although small reductions in DNA content were reported previously in some cases (Schultz, 1941;Ananiev and Gvozdev, 1974;Cowell and Hartmann-Goldstein, 1980;Kornher and Kaufman, 1986) other workers detected no evidence for changes in copy number (Cole and Sutton, 1941;Henikoff, 1961;Rushlow et al, 1984). Most measurements were made at an unknown distance from the inducing breakpoint.…”
Section: A Variegated Position Effect Reduces the Copy Number Of Somementioning
confidence: 84%
“…Although local changes in the appearance of variegating polytene chromosomes are easily seen (Prokofyeva-Belgovskaya, 1939;Schultz and Caspersson, 1939) only small changes in DNA copy number, at most 2-to 3-fold, have been reported (Cowell and Hartmann-Goldstein, 1980;Kornher and Kaufman, 1986). After correcting for changes in chromatin structure, Henikoff (1981) detected no differences in the polytenization of a variegating heat shock puff.…”
Section: Introductionmentioning
confidence: 99%
“…The compact packaging of heterochromatin is extended into the adjoining euchromatic region resulting in repression of the affected loci. Modifiers such as temperature, amount of Y chromosome heterochromatin and mutations display identical effects on phenotypic variegation and heterochromatinization at the chromosomal level (Hartmann-Goldstein 1967;Cowell and Hartmann-Goldstein 1980;Reuter et al 1982a;Zhimulev et al 1986). Variegated mutant expression of the affected genes reflects not only high variability but also clonal initiation of heterochromatinization (Janning 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Tetraploid is an organism with four chromosome groups in somatic cells. It has been shown that the tetraploid cells had chromatin instability owing to the difficulties in dividing genomes with double number of centrosomes and chromosomes ( Cowell 1980 ; Mayer and Aguilera, 1990 ; Fujiwara et al, 2005 ; Margolis 2005 ; Storchova et al, 2006 ; Coward and Harding 2014 ). In general, an increasing nuclear DNA content has important effects on gene expression in cells ( Hancock, Martin, and Lelchuk 1993 ).…”
Section: Discussionmentioning
confidence: 99%